2006
DOI: 10.1007/s00359-006-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical reconfiguration mediates swallowing and rejection in Aplysia californica

Abstract: Muscular hydrostats, such as tongues, trunks or tentacles, have fewer constraints on their degrees of freedom than musculoskeletal systems, so changes in a structure's shape may alter the positions and lengths of other components (i.e., induce mechanical reconfiguration). We studied mechanical reconfiguration during rejection and swallowing in the marine mollusk Aplysia californica. During rejection, inedible material is pushed out of an animal's buccal cavity. The grasper (radula/odontophore) closes on inedib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…As the I2 muscle is activated it shortens, and thus it loses mechanical advantage and its force is reduced because of its length/tension property (Neustadter et al 2007;Novakovic et al 2006;Sutton et al 2004;Yu et al 1999). Closure of the grasper changes the grasper shape from roughly spherical to roughly ellipsoidal (compare Fig.…”
Section: What Variations In the Motor Program Affect Motor Behavior?mentioning
confidence: 99%
See 2 more Smart Citations
“…As the I2 muscle is activated it shortens, and thus it loses mechanical advantage and its force is reduced because of its length/tension property (Neustadter et al 2007;Novakovic et al 2006;Sutton et al 2004;Yu et al 1999). Closure of the grasper changes the grasper shape from roughly spherical to roughly ellipsoidal (compare Fig.…”
Section: What Variations In the Motor Program Affect Motor Behavior?mentioning
confidence: 99%
“…Closure of the grasper changes the grasper shape from roughly spherical to roughly ellipsoidal (compare Fig. 6, top, 2nd and 3rd panels), elongating the I2 muscle and thus enhancing I2's ability to protract (Neustadter et al 2007;Novakovic et al 2006).…”
Section: What Variations In the Motor Program Affect Motor Behavior?mentioning
confidence: 99%
See 1 more Smart Citation
“…Because we established many of the neural and biomechanical mechanisms that underlie swallowing responses of different amplitude in the marine mollusk Aplysia californica (Ye et al, 2006), we sought to determine how these properties changed during a qualitatively different behavior, rejection. Magnetic resonance (MR) imaging showed that the central grasper (radula/odontophore) changes shape from spherical when it is open to ellispsoidal when it is closed (Neustadter et al, 2002b;Novakovic et al, 2006). We hypothesized that grasper shape change may alter the shapes and positions of surrounding muscles, and this mechanical reconfiguration is crucial for the neural control of rejection (Novakovic et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Magnetic resonance (MR) imaging showed that the central grasper (radula/odontophore) changes shape from spherical when it is open to ellispsoidal when it is closed (Neustadter et al, 2002b;Novakovic et al, 2006). We hypothesized that grasper shape change may alter the shapes and positions of surrounding muscles, and this mechanical reconfiguration is crucial for the neural control of rejection (Novakovic et al, 2006).…”
Section: Introductionmentioning
confidence: 97%